2019
DOI: 10.1016/j.powtec.2018.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using marine sediments in SCC pastes as supplementary cementitious materials

Abstract: In the context of the depletion of natural geomaterials, the increasing amount of dredged sediments calls for seeking new possibilities for treating and recycling these materials as cementitious supplementary materials. The aim of this paper is to design ecological SCC pastes, which require less cement, incorporating treated marine sediments. Despite many approaches investigating the ultimate formula of self-compacting concrete (SCC), the process remains complex because it is based on many variables and compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…These reductions in compressive strength were reduced to 92.73% at 90 days. These same results are consistent with what has been described in the literature regarding the substitution of cement by slag [12,68] and calcined sediments [69,70].…”
Section: Compressive Strength Of Mortarssupporting
confidence: 93%
“…These reductions in compressive strength were reduced to 92.73% at 90 days. These same results are consistent with what has been described in the literature regarding the substitution of cement by slag [12,68] and calcined sediments [69,70].…”
Section: Compressive Strength Of Mortarssupporting
confidence: 93%
“…Previous investigations on pastes and mortars [20,21] revealed that dredged marine sediments did not show negative effect on fresh properties when the water demand of sediment is taken into account. Using a multi-objective optimization for workability properties and compressive strength development at different ages, an optimal substitution content of 7% to 35% were reported in the case of binder content ranging between 380 and 600 kg/m 3 and water-to-cementitious materials (w/cm) of 0.32 and 0.34.…”
Section: Research Significancementioning
confidence: 93%
“…Optimization algorithms including the deterministic simplex method and the stochastic genetic method were applied to determine the parameters in the Herschel-Bulkley model for fresh cement suspensions [9]. Multi-objective optimization methods, such as support vector regression (SVR), model tress (MT), M5 model rules, mix and design approach, particle swarm optimizations (PSO) and response surface method (RSM) are also used in cement chemistry and hydration processes to obtain optimal chemical combination and proportion for better cement performance, workability, and energy consumptions [201,[301][302][303][304].…”
Section: Discussionmentioning
confidence: 99%